PERLINDUNGAN HUKUM DEBITUR WANPRESTASI PADA PERJANJIAN KREDIT RUMAH ATAS JAMINAN HAK TANGGUNGAN - Ervira Sekar Langit; Erny Herlin Setyorini (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
A credit agreement is a facility from a bank to make it easier for debtors to get a loan from a bank, be it a loan for a business or a loan for buying a house. Collateral at the bank will be kept by the bank in order to bind a debtor to comply with the credit agreement and so that there is no default, but looking at the length of a home loan agreement, not many debtors are in default, therefore the guarantee granted to the bank will be kept by the bank. bank and if there is a default, the bank will sell the debtor's interference to other debtors, either by auction or sold without an auction, there is also an overcredit made by the bank so that the loan that has been issued by the bank can be covered by other debtors. From several credit problems to over-credit by the bank, it is often found that there will be no legal protection for debtors who default, both in terms of guarantees and installments that have been paid. Therefore, the author feels that the problems that occur in the credit agreement at the bank really attract the attention of the author to know the process from the beginning of the credit agreement until the agreement is completed because of the achievements made by the debtor